Thermodynamic behavior of the Mg–Co–H system: The effect of hydrogen cycling - Verón, María Gisela (2014)
Thermodynamic properties of the Mg–Co–H system were investigated using equilibrium pressure measurements. Experimental determination of absorption and desorption pressure-composition isotherms (PICs) was carried out in the temperature range of 250–425 °C, using as starting material a 2Mg–Co mixture milled under argon and Mg2CoH5 produced by reactive ball milling of the 2MgH2–Co mixture. It was found that the cycling affects the PCIs shape and the total hydrogen storage capacity. XRPD analysis of the samples at different stage of the absorption PCIs reveals that the plateau at low hydrogen pressure is associated with the formation of Mg6Co2H11 and the plateau at higher hydrogen pressure corresponds to Mg2CoH5 formation. In addition, an intermediate plateau is also observed at 300 and 350 °C, which was related with the formation of MgH2 from MgCo intermetallic.